Analysis Of The Influence Of Price, Atmosphere, And Product Quality On Repurchase Interest Through Customer Satisfaction As An Intervening Variable In Bicoffee Coffee Shop & Resto - Ardiansyah, Syauqi; Ingkadijaya, Rahmat; Widyastuti, Novita (Jurnal Toursci, 2025)
Background. Currently, the food industry is highly popular in the city of Tangerang, as evidenced by the numerous restaurants that have emerged, both on a small scale and on a large scale. Aims. This study aims to analyze the influence of price, atmosphere, and product quality on repurchase interest, mediated by customer satisfaction, at BiCoffee Coffee Shop & Resto. Methods. The research was conducted using a quantitative method, collecting primary data through a questionnaire administered to customers of BiCoffee Coffee Shop & Resto. The variables analyzed included price, atmosphere, product quality, customer satisfaction, and repurchase interest. Result. The study's results show that the price, atmosphere, and quality of the product have a significant impact on customer satisfaction. Customer satisfaction has also been shown to have a considerable influence on repurchase interest. Conclusion. Additionally, it was found that customer satisfaction acts as an intervening variable in the relationship between price, atmosphere, product quality, and repurchase interest. Implementation. This research offers practical implications in the form of recommendations for BiCoffee Coffee Shop & Resto to enhance competitiveness through price optimization, an attractive atmosphere, and the provision of high-quality products, thereby increasing customer satisfaction and loyalty